Assessment of Natural Groundwater Recharge in Terengganu, Malaysia - Mohd Khairul Amri, Kamarudin; Muhammad Barzani, Gasim; Mohd Ekhwan, Toriman (2016)
Estimation of groundwater recharge is essential for efficient groundwater resources management, for domestic uses and irrigation purposes in the study area. The present research entails the assessment of natural groundwater recharge in Terengganu Malaysia. Estimation of recharge by whatever method is usually subjected to a large uncertainty and errors. However, this research attempt to derive an empirical relationship to determine the groundwater recharge from rainfall based on seasonal groundwater balance studies using the data obtained from 2000-2001 to 2011-2012. This empirical relationship similar to Chaturvedi formula was derived by fitting the estimated values of rainfall recharge, and the corresponding values of rainfall in the monsoon season through the non-linear regression techniques. The result shows that the proportion of variance explained was found to be 89.52 %, the recharge of groundwater commences at P = 15.28 inches and the relative errors was found to range from 3.680 to 46.020%.